Assessing the Distortions of Mandatory Pensions on Labor Supply Decisions and Human Capital Accumulation : How to Bridge the Gap between Economic Theory and Policy Analysis - Bodor, András; Robalino, David; Rutkowski, Michal (World Bank, Washington, DC, 2012)
Mandatory pension systems play a major role in individual savings and labor supply decisions. In particular, it is well known that defined benefit pension schemes, which are not actuarially fair, can create incentives for early retirement and therefore reduce labor supply and the stock of human capital in a given country. This is an important policy issue in middle-income countries, with still low participation rates in the labor force, where the "window" opened by the demographic transition is already closed or will close in the near future. In these countries, policies to stimulate private sector growth, competitiveness, and employment creation should be accompanied by policies that increase labor force participation, raising the ratio of active to inactive population and therefore the potential for higher income per capita growth. Unfortunately, the analytical tools developed to assess pension reform options tend to focus on the financial sustainability of the schemes and the adequacy of benefits. Little attention is given in practice to the social costs imposed by distortions on the supply of labor. In part, this is given by the lack of analytical tools that, in the context of limited information regarding individual preferences and behavior, can be used to assess the magnitude of these distortions. This paper develops methodologies that can bridge the gap between economic theory and the practices of pension policy personnel under conditions of deep uncertainty regarding the variables driving individual behavioral responses to policy changes. First, the paper develops an indicator to predict the age-specific retirement probabilities induced by a particular pension system, given heterogeneous individual preferences over risk, consumption, and leisure. The paper then describes how this indicator can be used to project the size of the labor force by gender, age and skill level and therefore the dynamics of human capital accumulation. The integration of these two analytical tools allow us to show the impact of a particular pension reform proposals on the dynamics of labor supply, human capital and, given the dynamics of capital and total factor productivity, economic growth. Furthermore, the paper develops a set of life-cycle income measures for typical individual paths that allow us to measure the contribution of segmented pension schemes to the segmentation of the labor market. The methods are applied to the case of Morocco.